2022
DOI: 10.1155/2022/6587165
|View full text |Cite
|
Sign up to set email alerts
|

Role of Traditional Cardiovascular Risk Factors after Initiation of Statin Therapy: A PharmLines Inception Cohort Study

Abstract: Background. Multiple studies and meta-analyses examined the role of traditional risk factors for cardiovascular events in statin treatment-naive patients. Nowadays, millions receive such therapy for the primary prevention of cardiovascular events (CVE). Objective. CVEs still occur in patients on primary preventive statin therapy. Therefore, further risk stratification within these patients is urgently needed. Methods. Using the unique linkage between biomedical data and prescription data from the PharmLines In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…The decreasing adherence of lipid lowering medication coincides with multiple studies on statin adherence [ 45 – 49 ]. Note that the rate of decrease is fairly similar to two studies conducted in the Netherlands despite using a (slightly) different population [ 46 , 48 ]. The view on decreasing adherence over time of antihypertensive medication is also in agreement with several studies on adherence of antihypertensive medication, although not all studies are conducted in a population of primary preventive patients [ 49 – 51 ].…”
Section: Discussionsupporting
confidence: 80%
“…The decreasing adherence of lipid lowering medication coincides with multiple studies on statin adherence [ 45 – 49 ]. Note that the rate of decrease is fairly similar to two studies conducted in the Netherlands despite using a (slightly) different population [ 46 , 48 ]. The view on decreasing adherence over time of antihypertensive medication is also in agreement with several studies on adherence of antihypertensive medication, although not all studies are conducted in a population of primary preventive patients [ 49 – 51 ].…”
Section: Discussionsupporting
confidence: 80%
“…In an exploratory study from our group using a small sample of patients (N = 602), we showed that modifiable risk factors of cardiovascular events at initiation of statin therapy such as LDL-C levels and blood pressure, did no longer play a role in the risk of cardiovascular events, if patients were persistent with this therapy ( Steenhuis et al, 2022 ). This was in line with earlier research done by Corrao et al, 2010 , Rannanheimo et al, 2015 , who estimated the effect of statin adherence on cardiovascular events in patients on primary preventive statin therapy, adjusted for time-independent risk factors as age, sex, drug dose and diabetes at baseline.…”
Section: Introductionmentioning
confidence: 99%